2016
DOI: 10.1007/s10689-016-9884-6
|View full text |Cite
|
Sign up to set email alerts
|

High microsatellite instability (MSI-H) colorectal carcinoma: a brief review of predictive biomarkers in the era of personalized medicine

Abstract: Approximately 15 % of colorectal carcinomas (CRC) display high level microsatellite instability (MSI-H) due to either a germline mutation in one of the genes responsible for DNA mismatch repair (Lynch syndrome, 3 %) or somatic inactivation of the same pathway, most commonly through hypermethylation of the MLH1 gene (sporadic MSI-H, 12 %). Although heterogeneous, MSI-H colorectal carcinomas as a group show some distinct biologic characteristics when compared to CRC with stable or low level microsatellite instab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 58 publications
2
110
0
6
Order By: Relevance
“…As Lynch syndrome–associated MSI-H tumors have been shown to have higher somatic mutation burden, 12,77 we performed additional analyses to detect potential hypermutation in MSI-H ACC, CESC, and MESO. Somatic variant calling was performed on whole-exome samples from these four cancer types, and the mean absolute number of somatic mutations—both nonsynonymous and synonymous—was found to be increased among MSI-H versus MSS tumors within their own cohorts (Fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…As Lynch syndrome–associated MSI-H tumors have been shown to have higher somatic mutation burden, 12,77 we performed additional analyses to detect potential hypermutation in MSI-H ACC, CESC, and MESO. Somatic variant calling was performed on whole-exome samples from these four cancer types, and the mean absolute number of somatic mutations—both nonsynonymous and synonymous—was found to be increased among MSI-H versus MSS tumors within their own cohorts (Fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…It was generally acknowledged that the numbers of mitochondria showed an increase in high metabolism cells like heart muscle cells. Adequate amounts of energy were a necessary precondition for the uncontrolled rapid proliferation of cancer cells [50]. The number of mitochondria, such logic goes, was increased in the cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies had shown that nuclear genome microsatellite instability was the significant predictor of prognosis CRCs [50, 72]. Much work remains to be done to make the definitive relationship between the mtMSI and nMSI clear.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapies are active in patients with MSI-H mCRC [34]. Based on its durable responses and long-term survival benefit, the anti-programmed cell death 1 receptor (PD-1) monoclonal antibody pembrolizumab was recently approved by the US FDA for use in adult and paediatric patients with unresectable or metastatic, MSI-H or MMR-deficient solid tumours that have progressed following prior treatment and who have no other satisfactory alternative treatment options, or in patients with CRC that has progressed following treatment with a fluoropyrimidine, oxaliplatin, and irinotecan [35,36].…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%